Opioid prescribing is excessive and variable after pediatric ambulatory urologic surgery. Issue 2 (April 2021) - Corona, Lauren E.; Roth, Elizabeth B.; Thao, Angela; Lin, Muzi; Lee, Ted; Harbaugh, Calista; Gadepalli, Samir; Waljee, Jennifer; Streur, Courtney S.
Summary: Background: Acute pain after surgery is one of the most frequent indications for opioid prescribing in children. Opioids are often not stored or disposed of safely after their use, placing children and others in the home at risk for accidental ingestion or intentional misuse. We currently lack evidence-based guidelines for post-operative pain management after common ambulatory pediatric urologic procedures. Thus, each surgeon must decide if and how much opioid to prescribe based on his/her own assumptions of perceived post-operative pain. Objectives: As part of an effort to establish opioid prescribing guidelines across two academic centers, the objectives of this study were to evaluate current variability in pediatric urologists' opioid prescribing factors and identify patients at greatest risk of being prescribed high doses of opioids after common ambulatory pediatric urologic procedures. Methods: We retrospectively evaluated post-operative opioid prescribing patterns after common ambulatory pediatric urology procedures (circumcision, orchiopexy, and hernia/hydrocele) at two major children's hospitals. Specifically, we evaluated if and how much opioid was prescribed for all children (18 years or younger) between 2016 and 2017. Bivariate analysis was performed using Kruskal–Wallis Test and Wilcoxon Rank Sum. Multivariable logistic regression was performed to determine patient, surgeon, and procedural factors that predicted the prescription of a high dose of opioids (greater than the median number of doses prescribed for that procedure). Results: Over the two-year period, 811 circumcisions and 883 inguinal surgeries (inguinal orchiopexy and hernia/hydrocele) were performed. 94% of patients undergoing circumcision and 97% of those undergoing inguinal surgery were prescribed opioid analgesia. The median number of doses prescribed for circumcision was 20; for inguinal surgeries, 23.75% of patients received 15 opioid doses or more. Patients ages 0–2 years, who represented the largest age group (41% of all patients), received significantly more opioid doses than all other age groups, followed by those >10 years (p < 0.01). There was significant variation in opioid prescribing patterns by provider (p < 0.01) (Figure 1) On multivariable logistic regression, younger age, pill form, and earlier year were all associated with a greater number of opioid doses prescribed for all surgeries. Conclusions: Across two institutions without a formal post-operative opioid prescribing policy for ambulatory pediatric urologic procedures, we observed considerable variability in provider prescribing patterns, with nearly all patients receiving an opioid, and those 0–2 years receiving the highest number of doses. This highlights the need for evidence-based guidelines for post-operative pain management after ambulatory pediatric urologic surgeries.